The genetic background influences the cellular and humoral immune responses to vaccines - Zeng, M. (Clin Exp Immunol, 2016)
The assessment of Toll‐like receptor (TLR) agonists as candidate adjuvants for induction of effective T helper type 1 (Th1) immunity continues to rely on the use of mice. However, the genetic variation among inbred mice may influence the efficacy of adjuvants and bias a study's conclusions. Here, we evaluated the differences in cellular and humoral responses of genetically non‐identical mouse strains immunized with ovalbumin (OVA) plus alum, TLR‐3, TLR‐4, TLR‐7/8 or TLR‐9 agonists. We found that all the tested TLR agonists recruited dendritic cells (DCs) and natural killer (NK) cells significantly into the lymph nodes, promoted DC–NK cross‐talk and enhanced the cellular responses in B6 strain. In contrast, TLR‐3 and TLR‐7/8 were the only two agonists that showed the cellular adjuvanticity in the BALB/c strain. Compared with other TLR agonists, TLR‐3 and TLR‐7/8 were demonstrated to be the most effective adjuvants to generate interferon (IFN)‐γ‐producing effector NK, CD4, and CD8 T cells in B6 and BALB/c strains, respectively. We also found that compared with alum, all adjuvants induced the recruitment of B cells and production of OVA‐specific immunoglobulin (Ig)G2a more effectively in both strains. In addition, the B6 strain recruited more B cells, but surprisingly produced significantly lower amounts of OVA‐specific IgG2a in response to all adjuvants. However, consistent with the frequency of IFN‐γ‐producing effector cells observed in individual strains following immunizations, we detected more OVA‐specific IgG2a in serum of B6 and BALB/c strains in response to TLR‐3 and TLR‐7/8, respectively. Our data suggest that genetic background should be taken into consideration when evaluating the activities of TLR agonists for the development of prophylactic and therapeutic vaccines.